2015
DOI: 10.1371/journal.pone.0120568
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for a Core Outcome Set for Measuring Standing Balance in Adult Populations: A Consensus-Based Approach

Abstract: BackgroundStanding balance is imperative for mobility and avoiding falls. Use of an excessive number of standing balance measures has limited the synthesis of balance intervention data and hampered consistent clinical practice.ObjectiveTo develop recommendations for a core outcome set (COS) of standing balance measures for research and practice among adults.MethodologyA combination of scoping reviews, literature appraisal, anonymous voting and face-to-face meetings with fourteen invited experts from a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 69 publications
0
58
0
Order By: Relevance
“…24 It was recently recommended by an international expert panel as suitable for a core outcome set or minimum data set for research and practice in adult populations. 69 Neither of these pediatric studies reported any adverse events in using either version of the BESTest. Given their inclusion of missing components in existing pediatric balance measures, comprehensiveness, and endorsed use in adult populations, one or both represent good candidates for initial validation in pediatric populations.…”
Section: Discussionmentioning
confidence: 86%
“…24 It was recently recommended by an international expert panel as suitable for a core outcome set or minimum data set for research and practice in adult populations. 69 Neither of these pediatric studies reported any adverse events in using either version of the BESTest. Given their inclusion of missing components in existing pediatric balance measures, comprehensiveness, and endorsed use in adult populations, one or both represent good candidates for initial validation in pediatric populations.…”
Section: Discussionmentioning
confidence: 86%
“…The ability to measure outcomes using a shorter instrument has many practical advantages over long-form instruments, for example better acceptability for the study population and better feasibility for the administering staff (Pollock et al, 2011;Rolstad et al, 2011). For these reasons, the MiniBESTest has increasingly been used and validated to assess balance impairments in several conditions (including a series of neurological diseases), and has recently been identified as the most comprehensive balance measure by different research groups (Pardasaney et al, 2013;Sibley et al, 2015aSibley et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Three of every 10 (29.6%) participants had sustained previous hip fractures, and four of every five (81.5%) used mobility devices, such as wheelchairs and walkers ( Table 1). The median [interquartile range (IQR)] number of attended sessions was 34 (30)(31)(32)(33)(34)(35)(36)(37). The participants performed high-intensity strength exercises at a median (IQR) of 16 (3.5-27.0) sessions and high-intensity balance exercises at a median (IQR) of 24 (11.0-31.5) sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Another consideration is whether the selected measure (the BBS) actually captured the effect of exercise for all participants. A review, however, confirmed the suggested use of the BBS as a core measure of functional balance outcomes in adults (37). Furthermore, the dichotomization of outcome variables has disadvantages; data variety is lost, and participants with deteriorated balance are equalized with those with balance improvement below the MDC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation